Інституціональні проблеми та протиріччя процесу реформування національного ринку праці в Україні - Сибірцев, В. В.; Sybirtsev, V. (My University, 2018)
Узагальнено інституціональні проблеми та протиріччя процесу реформування національного ринку праці в Україні. Визначено склад актуальних тенденцій формування нових і реформування традиційних інститутів, функціонування яких орієнтоване на регулювання розвитку національного ринку праці. Встановлено специфічність природи та змісту інституціональних перетворень, що знаходять прояв в окремих соціетальних полях і механізмах взаємодії економічних агентів під час реалізації інституціональних реформ, як в цілому у макроекономічному аспекті, так і в секторальних проявах. Доведено фазовий (обумовлений динамічністю протікання фаз циклу відтворення робочої сили, до складу яких відносять етапи формування, розподілу, обміну та використання трудових ресурсів) характер походження фундаментальних суспільних протиріч у розвитку національного ринку праці. Визначено склад і розглянуто сутність ключових інституціональних конфліктів при реформуванні національного ринку праці. The article presents a generalization of institutional problems and contradictions in reforming the national labor market in Ukraine. The composition of current trends in the formation of new and the reformation of traditional institutions, whose functioning is focused on regulating the development of the national labor market, is determined. There defined the specificity of the nature and content of the institutional transformations, which manifest themselves in the separate societal fields and mechanisms of interaction of economic agents in the course of implementing the institutional reforms both in the macroeconomic context in whole and in the sectoral one. There proved a phase character of the emergence of fundamental social contradictions in the development of the national labor market (i.e. its character is stipulated by the dynamics of the phases of the labor force reproduction cycle, which include the stages of formation, distribution, exchange and use of labor resources). The composition of the key institutional conflicts in reforming the national labor market is determined, their nature considered.
Іnstitutional problems and contradictions in reforming the national labor market in Ukraine
Keywords: розвиток; ринок праці; державне регулювання; інституціональні зміни; інституціональне регулювання; development; labor market; state regulation; institutional changes; institutional regulation